2006
DOI: 10.1021/np0600090
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Withanolides fromJaborosarotacea

Abstract: Twelve new withanolides were isolated from the aerial part of Jaborosa rotacea: five had a spiranoid delta-lactone (1-5); one contained a 26,12-delta-lactone and a C-12-C-23 bond (6); five corresponded to trechonolide-type withanolides with configuration at C-23 opposite of those previously isolated (7, 8, 10-12); two of these have an additional oxido-bridge between C-21 and C-24; finally a withanolide with a hemiketal ring formed between a 21-hydroxyl and a 12-ketone (13) and the closely related jaborosalacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 19 publications
3
61
0
1
Order By: Relevance
“…Tettamanzi et al had reported the isolation of a closely related epoxyg-lactol from J. lanigera for which the (23R) configuration was proposed (175); this compound had 13 C NMR data identical to 382 for C-12-C-18 and C-20-C-28 indicating that both compounds should have the same configuration in the side chain, hence the revised structure 386 is proposed. Thus so far, all known epoxy-g-lactones and lactols have the same configuration at C-23, opposite to that of trechonolide A. Jaborosalactones 35 (387) and 36 (388) isolated from J. rotacea would result from cyclization of a 21-hydroxy-epoxy-g-lactone (120). It should be noted that to date, trechonolides have been reported in nine of the thirteen Jaborosa species studied.…”
Section: Trechonolidesmentioning
confidence: 97%
See 3 more Smart Citations
“…Tettamanzi et al had reported the isolation of a closely related epoxyg-lactol from J. lanigera for which the (23R) configuration was proposed (175); this compound had 13 C NMR data identical to 382 for C-12-C-18 and C-20-C-28 indicating that both compounds should have the same configuration in the side chain, hence the revised structure 386 is proposed. Thus so far, all known epoxy-g-lactones and lactols have the same configuration at C-23, opposite to that of trechonolide A. Jaborosalactones 35 (387) and 36 (388) isolated from J. rotacea would result from cyclization of a 21-hydroxy-epoxy-g-lactone (120). It should be noted that to date, trechonolides have been reported in nine of the thirteen Jaborosa species studied.…”
Section: Trechonolidesmentioning
confidence: 97%
“…), thus the methyl ketal 255 is probably formed during isolation. Nicotra et al reported the isomeric clorohydrin, jaborosalactone 37 (256), from Jaborosa rotacea (120). Interestingly, the D 2 -withanolide 257 was present in Jaborosa caulescens var.…”
Section: Withametelins and Sativolidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Estes foram primeiramente citados na literatura em 1962, mas sua elucidação estrutural só aconteceu em 1966 com a descrição estereoquímica da vitaferina 1 (Figura 1) isolada das folhas de Withania somnifera, popularmente conhecida na Índia como Ashwaganha. 2 Os vitanolidos têm sido isolados de plantas de vários gêneros, como exemplo podem ser citados: Acnistus, [3][4][5][6][7][8] Datura, 9 Jaborosa, 10 Physalis 11 e Withania, 12,13 todos da família Solanaceae, e despertam interesse por apresentarem diversas atividades biológicas, algumas delas como antitumoral, 4-8 diurética, 13 indução de quinona redutase 5,14 e imunossupressora. 15 Outros esteroides que são encontrados na famíla Solanaceae incluem glicosídeos e alcaloides esteroidais, compostos presentes nos gêneros Cestrum e Solanum, sendo este último gênero o que possui o maior número de espécies catalogadas.…”
Section: Introductionunclassified